Opinions of socially excluded individuals on conducting business activity and being employed on a full-time basis in view of own research - Szewczyk-Jarocka, Mariola (Opinie osób wykluczonych społecznie na temat działalności gospodarczej i pracy na etacie w świetle badań własnych, 2019)
The main objective of the considerations presented in the article is the attempt to verify the opinion of excluded individuals on conducting a business activity and being employed on a full-time basis. Detailed objectives concerning the analysis of the opinions of those surveyed were also adopted together with an assessment of the types of economic activity that the participants of the survey would like to conduct. The results of the questionnaires obtained from 350 respondents. As a result of the analyses, the author concluded that women as well as respondents with a secondary education more often express the will to take up a fulltime job. Statistically significant differences were recorded when it comes to the assessment of hairdressing and beauty care services between the persons with university education and those with secondary education as well as those without it. Statistically significant differences were also recorded in the context of taxi services between the persons without a secondary education and the persons with a university and secondary education. What is more, statistically significant differences were recorded in the assessment of childcare or caring for the elderly as well as the assessment of construction servicesThe main objective of the considerations presented in the article is the attempt to verify the opinion of excluded individuals on conducting a business activity and being employed on a full-time basis. Detailed objectives concerning the analysis of the opinions of those surveyed were also adopted together with an assessment of the types of economic activity that the participants of the survey would like to conduct. The results of the questionnaires obtained from 350 respondents. As a result of the analyses, the author concluded that women as well as respondents with a secondary education more often express the will to take up a fulltime job. Statistically significant differences were recorded when it comes to the assessment of hairdressing and beauty care services between the persons with university education and those with secondary education as well as those without it. Statistically significant differences were also recorded in the context of taxi services between the persons without a secondary education and the persons with a university and secondary education. What is more, statistically significant differences were recorded in the assessment of childcare or caring for the elderly as well as the assessment of construction services
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 90-101
Keywords: social exclusion; own research; full time employment; economic activity; wykluczenie społeczne; badania własne; praca na etacie; działalność gospodarcza